2022
DOI: 10.11628/ksppe.2022.25.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Physiological Responses of Pseudolysimachion pusanensis (Y. N. Lee) Y. N. Lee to NaCl Treatment

Abstract: Background and objective: This study was conducted to determine the effect of NaCl on the growth, antioxidants (superoxide dismutase, proline), maximum quantum yield, and chlorophyll contents of Pseudolysimachion pusanensis.Methods: Five levels of NaCl concentrations (0, 50, 100, 200, 400 mM) were used for treatment. Results: The growth according to NaCl concentrations was highest at 50 and 100 mM, but root growth declined before the top from 200 mM or higher. The increase in NaCl concentrations also led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Proline acts as an osmotic regulator that regulates the water potential of plants (Binzel et al, 1985), and it increases when plants are under water stress (Kwon et al, 2022;Jin et al, 2017). For Farfugium japonicum (L.) Kitam., SOD, POD, and MDA increased in the 0.2 m 3 ⋅m -3 treatment in dry state, but there was not much difference in SOD and MDA from the 0.4 m 3 ⋅m -3 treatment plot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proline acts as an osmotic regulator that regulates the water potential of plants (Binzel et al, 1985), and it increases when plants are under water stress (Kwon et al, 2022;Jin et al, 2017). For Farfugium japonicum (L.) Kitam., SOD, POD, and MDA increased in the 0.2 m 3 ⋅m -3 treatment in dry state, but there was not much difference in SOD and MDA from the 0.4 m 3 ⋅m -3 treatment plot.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of horticulture, various studies have been conducted to achieve efficient control of soil moisture content. Some research took approaches based on substrate properties, such as using soil moisturizing agents to enhance soil moisture retention (Kwon et al, 2022). Studies have also been carried out to determine the optimal irrigation timing based on the measurement of volumetric water content (VWC) using automated irrigation systems (Nam et al, 2017;Nam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Humidity monitoring has garnered significant attention owing to its critical role across both the living systems and the industrial processes, including environment monitoring, agriculture, electronics industry, manufacturing process, food industry, medical industries, energy harvesting, and so on. [ 1–5 ] The different application scenarios need different monitoring techniques, for example, for earth humidity monitoring, such remote techniques as microwave, millimeter, and terahertz (THz), should be employed to provide all‐weather observations of the atmosphere on a global basis; [ 6,7 ] while in human daily lives for such fields as food storage, concrete structures, the internet of things (IoT), electronic devices, respiration monitoring, disease diagnosis, and treatment, the humidity monitoring and evaluating require the sensitive materials with the features of short response and recovery times, as well as diverse‐configuration compatibility, that can meet the spatial and temporal humidity gradients measurements. [ 8–15 ] To date, many efforts have been performed for the fabrication of sensitive materials, including metal oxides, ceramics, perovskites, carbon compounds, and organic polymers, to realize high‐performance humidity monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several solo, binary, and ternary solvents have been introduced without DMF to prepare various compositions of green perovskite inks. [13,[15][16][17][18][19][20][21] Sun et al employed a mixture of methylammonium acetate and ACN to fabricate high-performance MAPbI x Br 3−x devices, in which the ACN minimized the coordination of the solvent and perovskite solutes that led to the formation of large micelles. [22] Cassella et al demonstrated up to 18.0% efficiency for the MAPbI 3 PSCs from a binary solvent of 2-ME and tetrahydrofuran.…”
Section: Introductionmentioning
confidence: 99%